The composition of government spending and the multiplier at the Zero Lower Bound - Julien Albertini; Arthur Poirier; Jordan Roulleau-Pasdeloup (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
We investigate the size of the multiplier at the ZLB in a New keynesian model. It ranges from around -0.25 to +1.5, depending on the extent to which government spending is productive, substitutable or not for private consumption.
Keywords: E31; E32; E52; E62; 330; Zero lower bound; New Keynesian; Government spending multiplier